Biomaterials approaches to treating implant-associated osteomyelitis. (March 2016) - Inzana, Jason A.; Schwarz, Edward M.; Kates, Stephen L.; Awad, Hani A.
Abstract: Orthopaedic devices are the most common surgical devices associated with implant-related infections and Staphylococcus aureus ( S. aureus ) is the most common causative pathogen in chronic bone infections (osteomyelitis). Treatment of these chronic bone infections often involves combinations of antibiotics given systemically and locally to the affected site via a biomaterial spacer. The gold standard biomaterial for local antibiotic delivery against osteomyelitis, poly(methyl methacrylate) (PMMA) bone cement, bears many limitations. Such shortcomings include limited antibiotic release, incompatibility with many antimicrobial agents, and the need for follow-up surgeries to remove the non-biodegradable cement before surgical reconstruction of the lost bone. Therefore, extensive research pursuits are targeting alternative, biodegradable materials to replace PMMA in osteomyelitis applications. Herein, we provide an overview of the primary clinical treatment strategies and emerging biodegradable materials that may be employed for management of implant-related osteomyelitis. We performed a systematic review of experimental biomaterials systems that have been evaluated for treating established S. aureus osteomyelitis in an animal model. Many experimental biomaterials were not decisively more efficacious for infection management than PMMA when delivering the same antibiotic. However, alternative biomaterials have reduced the number of follow-up surgeries, enhanced the antimicrobial efficacy by delivering agents that are incompatible with PMMA, and regenerated bone in an infected defect. Understanding the advantages, limitations, and potential for clinical translation of each biomaterial, along with the conditions under which it was evaluated (e.g. animal model), is critical for surgeons and researchers to navigate the plethora of options for local antibiotic delivery.